Analysis of mutations and suppressors affecting interactions between the subunits of the HIV type 1 reverse transcriptase - Tachedjian, Gilda (National Academy of Sciences, 2000)
HIV-1 reverse transcriptase (RT) catalyzes the conversion of genomic RNA into cDNA. The enzyme is a heterodimer of p66 and p51 subunits, and the dimerization of these subunits is required for optimal enzyme activity. To analyze this process at the genetic level, we developed constructs that permit the detection of the interaction between these subunits in the yeast two-hybrid system. Genetic analysis of RT subdomains required for heterodimerization revealed that the fingers and palm of p66 were dispensable for p51 interaction. However, as little as a 26-amino acid deletion at the C terminus of p51 prevented dimerization with p66. A primer grip mutation, L234A, previously shown to inhibit RT dimerization by biochemical assays, also prevented RT dimerization in the yeast two-hybrid system. Second-site mutations that restored RT dimerization in yeast to the L234A parent were recovered in the tryptophan repeat region at the dimer interface and at the polymerase active site, suggesting the involvement of these sites in RT dimerization. In vitro binding experiments confirmed the effects of the L234A mutation and the suppressor mutations on the interaction of the two subunits. The RT two-hybrid assay should facilitate the extensive genetic analysis of RT dimerization and should make possible the rapid screening of potential inhibitors of this essential process.